2020
DOI: 10.3399/bjgp20x708113
|View full text |Cite
|
Sign up to set email alerts
|

Current practice and attitudes towards vaccination during pregnancy: a survey of GPs across England

Abstract: BackgroundAntenatal vaccines are commonly delivered in primary care, yet the views of GPs regarding these programmes have been neglected in research to date.AimTo establish the attitudes and current practice of GPs towards antenatal vaccination and their views on the optimal location for delivery of this service.Design and settingA multicentre online survey questionnaire.MethodA questionnaire was sent to GPs across England between December 2018 and January 2019.ResultsThe majority of 1586 responders considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Pediatricians with positive attitudes of meningococcal B vaccine (4CMenB) were five times more likely to recommend it [ 93 ], as were providers who believed vaccines are effective, beneficial, and safe [ 36 ]. HCPs who believed administering vaccination and advising patients about vaccines were their responsibility had increased recommendation [ 71 , 81 ], discussed vaccines more often [ 115 ], and perceived greater vaccine utility [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatricians with positive attitudes of meningococcal B vaccine (4CMenB) were five times more likely to recommend it [ 93 ], as were providers who believed vaccines are effective, beneficial, and safe [ 36 ]. HCPs who believed administering vaccination and advising patients about vaccines were their responsibility had increased recommendation [ 71 , 81 ], discussed vaccines more often [ 115 ], and perceived greater vaccine utility [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Female providers were often more likely to recommend or provide vaccines [ 50 , 60 , 97 , 98 ]; males were more likely to be nonadopters [ 99 ]. Some studies indicated positive vaccine behavior among older HCPs with more experience [ 49 , 73 , 81 ] (OR = 1.03) [ 111 ] or more years of practice (OR = 1.12–1.60) [ 65 , 72 , 100 , 115 ]. Other studies found HCPs over 50 years were less likely to recommend (OR = 0.49) [ 65 ] and recent graduates more likely (VE = 59%) [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…25,30,38 A recently reported survey of UK GPs also found that there was support among GPs for antenatal services to deliver maternal vaccine programs in England. 39 Other investigators have previously reported on vaccine clinics based within maternity services, for example Green et al described a midwife clinic based in Lewisham and Greenwich NHS Trust. 23 However, the authors did not analyze the demographics of women using the clinic nor reasons for acceptance or declining vaccination from the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…31 It should be noted that there remains a paucity of research regarding the views of GPs and family physicians toward the routine adoption of this approach. 20,42,43 This is important, as primary care-delivered vaccination has been the traditional model of care for many countries, and support from GPs will be needed to ensure smooth implementation of a new service (especially given that many GP practices currently receive funding for the administration of vaccines). However, some recent studies (including a large survey of English GPs) 43 have identified that many feel a sense of disconnect from antenatal care, and there is indeed support for maternity health-care professionals in the community and Secondary Care to take greater responsibility for the promotion and administration of the antenatal vaccination program, and to embed this within routine antenatal visits.…”
Section: What Are the Barriers To Routine Implementation Of This Apprmentioning
confidence: 99%
“…20,42,43 This is important, as primary care-delivered vaccination has been the traditional model of care for many countries, and support from GPs will be needed to ensure smooth implementation of a new service (especially given that many GP practices currently receive funding for the administration of vaccines). However, some recent studies (including a large survey of English GPs) 43 have identified that many feel a sense of disconnect from antenatal care, and there is indeed support for maternity health-care professionals in the community and Secondary Care to take greater responsibility for the promotion and administration of the antenatal vaccination program, and to embed this within routine antenatal visits. It is important to note, however, that even if antenatal vaccination programs are exclusively delivered within antenatal care, GPs will continue to have a role in providing advice to pregnant women opportunistically, and continued education of GPs will, therefore, be essential.…”
Section: What Are the Barriers To Routine Implementation Of This Apprmentioning
confidence: 99%